Towards a synthesized critique of forest‐based 'carbon‐fix' strategies. Issue 1 (21st February 2023) - Vian, Jessica Enara; Garvey, Brian; Tuohy, Paul Gerard
Abstract: This article synthesizes critiques of 'carbon‐fix' strategies in the forestry sector to clarify key concerns about reductionist treatments of forests and carbon and to facilitate further debate. It begins by asserting that since climate change mitigation has been placed at the centre of forest governance, forests have been deemed to serve as 'carbon‐fixing' devices in ways that can be discerned across three distinct but inter‐related categories: (i) carbon storage devices, (ii) carbon removal devices and (iii) net‐zero bioenergy devices. A transdisciplinary literature review is used to shed light on key concerns relating to the instrumentalisation of forests within each of these categories. By doing so, this article contributes to a deeper understanding of why relegating forests to a 'carbon‐fix' function is insufficient to tackle climate change and, rather, poses threats to forest ecosystems and forest‐dependent communities. This review ultimately calls into question the use of forests to delay crucial systemic changes, without diminishing the importance of forest conservation, restoration, governance, as well as technological innovation, in mitigating the ongoing harmful effects of climate change. Abstract : This article synthesizes the main critiques of 'carbon‐fix' strategies in the forestry sector from social, natural and engineering disciplines. It shows that climate policies have compelled forests to function as 'carbon‐fixing' devices that store, remove and neutralize CO2 . However, these strategies have been ineffective in reducing atmospheric CO2 concentrations and exacerbated other social and environmental issues.